ANALYSIS OF ASTEROID’S OBSERVATIONS IN OPEN PHOTOMETRIC DATABASES - Pomazan, N.; Maigurova, N. (Одеські астрономічні публікації, 2016)
Today there are several open photometric databases containing important information for the study of the physical properties of asteroids. These databases are based on the results of various measurements of the different sets of objects. The study of statistical correlations between the various databases could significantly expand the list of asteroids with known physical parameters. We present the results of the comparative analysis of the determination of the albedo, diameters and absolute magnitudes of asteroids of five open sources (AKARI, IRAS, NEOWISE, HORIZONS and Pan-STARRS1). The infrared survey WISE (relatively to asteroids is NEOWISE project) and photometric survey Pan-STARRS1 are the widest databases of the absolute magnitudes and the albedo of asteroids providing information about 139356 and 248457 objects respectively. These surveys contain 73301 common asteroids. The obtained statistical relationships between the databases based on a common set of asteroids are presented.